Endogenous tyrosinase-catalyzed therapeutics - Yawen You; Zhaochen Guo; Yixin Wang; Sichen Yuan; Quanyin Hu (Nature Communications)
Abstract Tyrosinase (TYR) catalyzes the two initial steps of melanin synthesis from tyrosine in various organisms. However, overproduction, accumulation, and abnormal reduction of melanin can lead to severe diseases, particularly skin diseases, which makes tyrosinase a significant endogenous target in developing therapeutics to treat melanin-associated disorders. Herein, we devise a TYR-based in situ catalytic platform that can generate drugs intracellularly through an endogenous copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction. By taking advantage of the potent catalytic activity of TYR that is mechanistically validated by ab initio molecular dynamics (AIMD) theoretical calculation and experimental catalysis performance, we develop a TYR-catalyzed in-situ formed proteolysis-targeting chimeras (PROTACs) to degrade intracellular TYR protein to decrease melanin synthesis for treating hyperpigmentation and a TYR-catalyzed in-situ activated prodrug strategy to overcome drug resistance for melanoma therapy. In male mouse models, we show that this TYR-catalyzed therapeutics could efficiently alleviate skin hyperpigmentation within 48 h as well as resensitize the drug-resistant melanoma cells to chemotherapeutics to control tumor growth. Together, we offer an integrative platform to leverage the catalytic activity of endogenous TYR to generate therapeutics through in situ bioorthogonal chemistry for treating melanin-associated skin diseases.